The impact of ice structures and ocean warming in Milne Fiord - J. Bonneau; B. E. Laval; D. Mueller; Y. Antropova; A. K. Hamilton (The Cryosphere, 2025)
Arctic tidewater glaciers and ice shelves are undergoing rapid attrition, with warmer ocean temperatures playing an important role. However, the relationship between ocean temperature and ice structure retreat is complex and may change as the ocean warms and as the ice structure geometry evolves. In order to explore ice–ocean interactions and the impact of retreating ice structures in a glacial fjord, we use a numerical ocean model of Milne Fiord, which features an ice shelf and a tidewater glacier with a floating glacier tongue (part of which is detached). We model past, present, and potential future ice configurations. Our results reveal that the average submarine melting is negligible across the ice shelf (<2 cm a−1) but can dominate thinning rates (>20 cm a−1) at specific locations where the ice is thick (>50 m) along the seaward edge. Our simulations also indicate that the temperature of water reaching the grounding line does not vary significantly when the ice shelf and glacier tongue are removed. In addition, we carry out a series of simulations with increasing ocean temperature which reveal a quasi-linear relationship between ocean temperature and submarine melting at the grounding line. Using this relationship and ocean temperature predictions for different greenhouse gas emission scenarios (2020 to 2100), we estimate that Milne Glacier will continue to retreat for at least 50 years, solely in response to ocean forcing. This study highlights the vulnerability of ice structures in the Arctic, even in a region regarded as the Last Ice Area.